ENERGY RELEASE RATE IN A PRESTRESSED SANDWICH PLATE-STRIP CONTAINING INTERFACE CRACKS - Akbarov, S. D.; Turan, A. (SPRINGER, 2009)
Within the frame work of a piecewise homogeneous body model, by utilizing the three-dimensional linearized theory of elasticity, the problem of opening of interface cracks in an initially stressed sandwich plate-strip is studied. To solve the corresponding boundary-contact problem, the FEM is employed. Numerical results for the influence of the initial stresses on the energy release rate (ERR) at various values of problem parameters are presented and discussed. In particular, it is established that the ERR in creases (decreases) with growing initial tension (compression) of the plate-strip.
Keywords: initial stresses; energy release rate; interface crack; sandwich plate; buckling delamination; FRACTURE; STRESS; MECHANICS; Materials Science; Polymer Science